Dissemination of Copernicus Land Monitoring data for Serbia through the development of geoportal on Cesium virtual globe - Milutinović Stefan R. (Tehnika, 2018)
Goal of this peper is dissemination of Copernicus Land Monitoring data for Serbia using modern web tehcnologies for developing responsive geospatial web application - geoportals. Peper describes importance of usage standardize geospatial data formats, geospatial veb services, geospatial metadata. System architecture is completely made using modern open-source application such as Geoserver, GeoNetwork for geospatial web services and Cesium JavaScript for visualizing geospatial data u 3D virtual globe. This kind of system architecture can be used to create quality, scalable geoportals for various applications.